A spatial emergent constraint on the sensitivity of soil carbon turnover to global warming - Rebecca M. Varney (Nature Portfolio, 2020)
The fate of the carbon locked away in soil is uncertain, and there are vast differences between models. Here the authors apply observational, spatio-temporal constraints on carbon turnover projections and find that uncertainty in estimations of carbon dynamics are reduced by 50%.